2014
DOI: 10.15193/zntj/2014/93/058-072
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Fat Deposit Within Carcass, Content of Intramuscular Fat, Fatty Acid Profile, and Tenderness of Rabbit Meat

Abstract: S t r e s z c z e n i eCelem pracy była ocena zależności między otłuszczeniem poszczególnych partii tuszki króliczej a zawartością tłuszczu śródmięśniowego, profilem kwasów tłuszczowych i kruchością mięsa królików rasy nowozelandzkiej białej (NB) i popielniańskiej białej (PB). Badaniami objęto po 20 osobników z każdej rasy. Króliczęta po odsadzeniu w 35. dniu żywiono do 90. dnia życia ad libitum pełnoporcjowymi mieszankami paszowymi o zawartości: 15,3 % białka ogólnego, 3,55 % tłuszczu surowego i 11,5 % włókna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
2
1
0
1
Order By: Relevance
“…Also in this study, the fat content was low in all cuts except brisket (Table 1). Highest content of fat in brisket and much higher than in our study (12.8%) was reported also by others (Kowalska et al, 2014;Pla et al, 2004). That difference Table 1.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Also in this study, the fat content was low in all cuts except brisket (Table 1). Highest content of fat in brisket and much higher than in our study (12.8%) was reported also by others (Kowalska et al, 2014;Pla et al, 2004). That difference Table 1.…”
Section: Resultssupporting
confidence: 79%
“…Those authors also reported the lowest fat content in loin compared with other cuts (1.20-1.52%). The fat contents in hind leg cuts shown in Table 1 were similar to those reported by Pla et al (2004) but much higher than in the New Zealand breed (0.69%; Daszkiewicz et al, 2011;Kowalska et al, 2014). Our results are confirmed by those reported by Alasnier et al (1996) who found that glycolytic muscles, dominating in the loin (Longissimus dorsi), contain less lipids than oxidative muscles, dominating in hind legs (eg.…”
Section: Componentssupporting
confidence: 91%
See 1 more Smart Citation
“…Daging yang digunakan dalam penelitian merupakan daging bagian kaki belakang dan loin, sebab pada bagian ini memiliki daging yang banyak serta merupakan bagian yang paling baik pada karkas kelinci. Hal ini sesuai dengan pendapat [24][9] bahwa daging bagian kaki belakang dan loin memiliki harga paling mahal dan digunakan untuk menilai kualitas daging kelinci. Hasil uji Kruskal-Wallis parameter warna dalam uji hedonik abon daging kelinci menunjukkan P<0,05 atau berbeda nyata.…”
Section: Hasil Dan Pembahasanunclassified